A novel fragile watermarking technique with high accuracy tamper localization - Erturkler, Metin; Tatar, Yetkin (Ieee, 2006)
Fragile watermarking techniques have been used in image authentication. In order to localize tamper region in image, most of the fragile watermarking techniques divide image into non-overlapping blocks and watermark each block independently. However, independence among blocks provides a potential for vector quantization counterfeiting attack. While dependence among blocks is established to prevent the attack, accuracy of tamper localization in image is considerably reduced. In this paper a novel fragile watermarking technique was proposed to increase accuracy of tamper localization by maintaining the dependence among blocks. In the proposed method, watermark which embedded in each block was composed of three digital signatures. This combining provided both security against vector quantization counterfeiting attack and increased accuracy of tamper localization. Obtained experimental results demonstrated that the proposed method is better than the methods using one and two dependent per block at accuracy of tamper localization.
Yüksek do?rulukta de?işim bölgesi belirlemeli yeni bir kirilgan filigranlama tekni?i
IEEE 14th Signal Processing and Communications Applications -- APR 16-19, 2006 -- Antalya, TURKEY
Keywords: Authentication